Transformation of sediment delivery and dispersal patterns controlled by relay-ramp evolution along the boundary fault of a lacustrine rift: The Eocene Shahejie formation, Dongying Sag, Bohai Bay Basin, NE China. (June 2021) - Li, Jin; Liu, Zhen; Liu, Jianping; Chen, Liang; Liu, Huimin; Huang, Lili; Qian, Liangliang; Lu, Kai; Liu, Keming
Abstract: The boundary fault of the Dongying Sag is divided into isolated and scattered segments and small-scale relay zones, which are important geomorphic features controlling sedimentation in the early stage of rift evolution. Previous studies have shown changes in facies in deposits of thousands of meters in thickness on fault-bounded margins, where deep-water fan systems are vertically stacked with delta deposits in the same way as in many basins around the world. However, changes in sedimentation processes and sedimentary systems and their relationship with the evolution of the main boundary fault remain a matter of debate. We focus on the transition from shallow-water to deep-water systems and their responses to relay-ramp evolution in the Yanjia Subsag of the Eocene Dongying Sag in the Bohai Basin. A relatively simple assemblage of local structures provides an ideal opportunity to investigate the impact of relay-ramp evolution on the early synrift deposits. An integrated dataset of 3D seismic volumes, cores and wireline logs is used to analyze the evolution of the Chennan Fault, to delineate thirteen lithofacies, and to recognize two depositional styles (including fan deltas and nearshore subaqueous fans) and their distribution during different stages of the relay-zone evolution. In the early stage of rifting, the depositional style changes, from the development of axial and transverse systems in the early to middle period to the development of transverse systems in the late period; this is mainly controlled by the evolution of the relay ramp. The change is accompanied by a rapid decrease in the rate of sediment supply, architectural changes in transport conduit from the relay ramp to a canyon, and local geomorphic changes that control transport routes, sediment delivery, and depositional locations. Floods ultimately become dominant transport mechanism with a new system, such that hyperpycnal flows form, leading to another transformation of the sedimentary systems from a fan-delta system to a nearshore subaqueous fan system. On the basis of these transformations in sedimentary systems we are able to propose new recommendations for reservoir exploration in continental rift basins, which include exploration potential, source reservoir cap assemblage, and spatiotemporal evolution of plays. Highlights: Sediment supply, conduits, and routes control by the relay ramp evolution along the boundray fault in a lacustrine. Transformation of flow properties and dispersal pattern control by the relay ramp evolution. The shallow-water to deep-water sedimentary model along the boundary fault is established in the early stage of rifting evolution where a transformation from axial systems to transverse systems is caused by relay ramp evolution.